2013
DOI: 10.1098/rsif.2013.0003
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering: a tool to detect in vivo thermal stress effects at the molecular dynamics level in micro-organisms

Abstract: In vivo molecular dynamics in Halobacterium salinarum cells under stress conditions was measured by neutron scattering experiments coupled with microbiological characterization. Molecular dynamics alterations were detected with respect to unstressed cells, reflecting a softening of protein structures consistent with denaturation. The experiments indicated that the neutron scattering method provides a promising tool to study molecular dynamics modifications in the proteome of living cells induced by factors alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…They are composed of several compartments (membrane, cytoplasm, skeleton, ribosomes), which are composed of lipids, cholesterol, proteins, nucleic acids, water, and numerous other molecules. Thus reproducibility of the experiments may be an issue, even when cells are prepared with the greatest care [23,24]. Neutron scattering experiments are long (typically several days) and usually require the isolation of the cells from nutriments or the use of physico-chemical conditions far from the cell optima.…”
Section: Summed Neutron Intensitiesmentioning
confidence: 99%
“…They are composed of several compartments (membrane, cytoplasm, skeleton, ribosomes), which are composed of lipids, cholesterol, proteins, nucleic acids, water, and numerous other molecules. Thus reproducibility of the experiments may be an issue, even when cells are prepared with the greatest care [23,24]. Neutron scattering experiments are long (typically several days) and usually require the isolation of the cells from nutriments or the use of physico-chemical conditions far from the cell optima.…”
Section: Summed Neutron Intensitiesmentioning
confidence: 99%
“…marismortui and of the native proteome from Hbt. salinarum [12][13][14][15][16] indicated that halophilic proteins display specific biophysical adaptation properties to high salt reflected by higher structural resilience, compared to mesophilic systems. It is likely, therefore, that most halophilic proteins display an obligatory requirement for high salt conditions in order to be active and stable.…”
mentioning
confidence: 99%
“…To use a mechanical analogy: in a collision between a moving billiard ball and one that is anchored by a spring, the force constant of the spring as well as the vibration amplitude of the anchored ball can be calculated from the changes in energy and momentum of the moving ball after it is ‘scattered’. Systems studied by neutron scattering include intrinsically disordered proteins, whole cells, membranes, nanoparticles and tissue222324252627.…”
mentioning
confidence: 99%